2017
DOI: 10.1186/s13034-017-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of attention-deficit–hyperactivity-disorder training program on the knowledge and attitudes of primary school teachers in Kaduna, North West Nigeria

Abstract: BackgroundThere are indications that teachers have limited knowledge about attention deficit hyperactivity disorder (ADHD), despite its high prevalence in childhood and its long-term effects on students such as academic underachievement, reduced self-esteem, and social and behavioural difficulties. This study is therefore aimed at assessing the effect of an ADHD training program on the knowledge of ADHD among primary school teachers in Kaduna, Nigeria and their attitudes towards pupils with ADHD.MethodsThis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 26 publications
11
40
3
Order By: Relevance
“…Studies were conducted in seven African or Middle Eastern countries and four Asian countries. Ten courses trained non-medical PHC staff, two trained doctors,9 10 one trained university student volunteers,11 one trained volunteer ‘champions’12 and another, school teachers 13. Sample sizes ranged from 12 in Sri Lanka to 1328 in the Philippines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were conducted in seven African or Middle Eastern countries and four Asian countries. Ten courses trained non-medical PHC staff, two trained doctors,9 10 one trained university student volunteers,11 one trained volunteer ‘champions’12 and another, school teachers 13. Sample sizes ranged from 12 in Sri Lanka to 1328 in the Philippines.…”
Section: Resultsmentioning
confidence: 99%
“…Course durations varied from 3 hours training for teachers about attention deficit hyperactivity disorder, followed by a 1.5-hour booster session,13 to 5 full days ‘base course’ followed by the mhGAP ‘standard course’16 or 40 hours child psychiatry training over 2 weeks 21. Most training lasted 2–3 days, combining didactic lecture teaching with videos, role plays, communication exercises and discussions.…”
Section: Resultsmentioning
confidence: 99%
“…Mental health professionals experienced an increase in referrals however, teachers were more likely to identify distressed students rather than students with mental illness (Moor et al, 2007). Studies aiming to improve teachers' knowledge of mental health showed significant increases in knowledge, attitudes, mental health literacy, and a decrease in stigma (Barbaresi & Olsen, 1998; Baum, Rotter, Reidler, & Brom, 2009; Eustache et al, 2017; Hussein & Vostanis, 2013; Jorm et al, 2010; Kutcher et al, 2016; Lasisi, Ani, Lasebikan, Sheikh, & Omigbodun, 2017; Powers et al, 2014). Furthermore, in one study, as many as 90% of teachers were more likely to share the information they gained from the training with a colleague after the training (Moor et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the early diagnosis and stable treatment are very critical, literature search indicates that ADHD is not early diagnosed among children until they started their studying life due to lack of parents and teacher knowledge' about the serious consequences of this disorder (13). Therefore, elementary school teacher is considered as a unique person for the early diagnosis and effective management of ADHD (14).…”
Section: Introductionmentioning
confidence: 99%
“…Elementary school teachers play an important role in the assessment of children's behavioral and academic problems due to their extensive interaction with children in a variety of unstructured and structured settings (16). Also, they play an crucial role in the implementation, support and assessment of recommended treatment plan for affected children (14). Furthermore, elementary school teachers make recommendations, inappropriate or appropriate, about ADHD to the parents, who tend to follow such recommendations (17).…”
Section: Introductionmentioning
confidence: 99%